Clinical correlation of optic nerve head analysis performed by SD-OCT in children with pseudopapilledema and papilledema - Ilter Iritas; Pinar A. Ozer; Çiğdem Genç Sel (Photodiagnosis and Photodynamic Therapy)
Purpose: To investigate some diagnostic indicators in optic nerve head (ONH) analysis of children with ‘Pseudopapilledema’ and ‘Papilledema’ by Spectral Domain Optical Coherence Tomography (SD-OCT). Methods: Medical records of 52 children with optic disc swelling, who were followed up by the departments of pediatric neurology and ophthalmology between May 2018 and May 2019 were reviewed retrospectively. Cases were classified as group 1 (Papilledema secondary to Idiopathic Intracranial Hypertension) including 54 eyes of 27 cases, group 2 (Pseudopapilledema secondary to bilateral optic disc drusen) including 50 eyes of 25 cases and control group. Three-dimensional imaging of ONH, peripapillary retinal nerve fiber layer (RNLF) thickness, Bruch's membrane opening height in the nasal respectively temporal quadrant (BMHN, BMH-T) levels were measured by SD-OCT and B-mode ocular ultrasonography data of all cases were evaluated. Results: When RNFL levels were compared between groups, nasal RNFL levels were found to be significantly higher in group 1 cases compared to group 2 (p < 0.001). In 3D imaging of the ONH among group 1 patients, the mean height of the apex in disc swelling was significantly higher than that of group 2 (p = 0,024). The apex in disc swelling was mostly observed to be localized at the middle and had a diffuse swelling pattern in group 1; whereas, in group 2, the it was localized mostly at the nasal quadrant. This variation was statistically significant (p < 0.001). When, Bruch's membrane opening height in the nasal respectively temporal quadrant (BMHN, BMH-T) levels were compared, the measurements obtained were found to be significantly higher in group 1 (p = 0,050 and p = 0,003 respectively). Conclusion: Nasal RNFL values of SD-OCT, Bruch's membrane opening height in the nasal respectively temporal quadrant (BMHN, BMH-T) levels, the location of the apex in disc swelling obtained by 3D analysis of the ONH are found to be potential diagnostic parameters when combined with clinical findings. It is important that the nasal quadrant elevation, where the highest peak in 3D imaging was measured, was higher in the papilledema group. The elevation of the optic disc peak in 3D imaging can be used as a parameter to help clinicians distinguish between optic disc drusen (ODD) and papilledema.